Trends in Stable Isotopes and Climate Proxies From Late Changhsingian Ghost Landscapes of the Karoo Basin, South Africa - Gastaldo, Robert A.; Tabor, Neil J.; Neveling, Johann (Frontiers in Ecology and Evolution, 2020)
The stable carbon- and oxygen-isotope values derived from in situ pedogenic carbonate-cemented nodules and vertebrate apatite in the Daptocephalus and overlying Lystrosaurus Assemblage Zones of the Balfour Formation, Karoo Basin, South Africa, have formed the basis for previous interpretations of a unidirectional climate trend toward hyper-aridity across the biozone boundary. This assemblage-zone boundary has been considered by many authors to be equivalent to the Permian–Triassic boundary in the basin. To better understand the climate under which these vertebrate assemblages existed, we have analyzed the carbon- and oxygen-stable isotopes of pedogenic carbonate nodules sampled from fourteen horizons of intraformational pedogenic nodular conglomerate (PNC) at Old Lootsberg Pass, a classic locality at which the Permian–Triassic boundary is reported. Analysis of these refractory soil constituents provides insight into the climate under which these “ghost” soils formed, where no other physical record of their existence is found in the stratigraphy. A positive correlation between δ13CVPDB and δ18OVSMOW values of micrite cements is defined by analyses of carbonate nodules taken from a measured stratigraphic thickness of ∼200 m, which spans the biozone boundary as currently defined. For samples taken from the same lag deposit, similar and relatively narrow ranges of isotope values are encountered. Samples cluster into two isotopic groups. The values in the first group cluster more tightly in all sampled nodules (δ13CVPDB −2.3 to −6.5‰; δ18OVSMOW 13.8–15.1‰), and are interpreted to indicate that these originated from paleosols that formed under similar climate controls. Values from the second sample group display a wider variance between analyses (δ13CVPDB −5.2 to 14.0‰; δ18OVSMOW 8.8–15.5‰). These nodules are interpreted to indicate that they originated under polygenetic soil-forming conditions representing the reworking of either: (1) more than one paleosol, the calcite-cemented nodules of which represent precipitation under both closed and open-system controls; or (2) one or more compound-composite paleosols. Stable-isotope trends based on PNCs analyzed, thus far, demonstrate an overall shift over time in the ghost landscapes. More seasonally dry soils formed under a climate that can be characterized as warm/dry accompanied by lower precipitation in the lower part of the section. In contrast, soils in the upper part of the section formed under cool and moist conditions, with increased precipitation near the biozone boundary. Hence, latest Permian climate associated with the more seasonally dry landscapes demonstrate a trend toward cooler and wetter conditions, which is opposite to the trend widely held in the literature.